2013
DOI: 10.1016/j.jaac.2012.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Meta-Analysis of the Functional Neural Correlates of Autism Spectrum Disorders

Abstract: Objective There is a pressing need to elucidate the brain–behavior interactions underlying autism spectrum disorders (ASD) given the marked rise in ASD diagnosis over the past decade. Functional magnetic resonance imaging (fMRI) has begun to address this need, but few fMRI studies have evaluated age-related changes in ASD. Therefore, we conducted a developmental analysis of activation likelihood estimation (ALE) meta-analysis to compare child versus adult ASD fMRI studies. We hypothesized that children and ado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
2
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(60 citation statements)
references
References 90 publications
3
52
2
3
Order By: Relevance
“…A recent study found that in children with ASD (aged 7-12 years old) there was a hyperconnectivity of the insula-based salience network 27 . The shift from the hyperconnectivity seen in younger children to hypoconnectivity seen in adolescents and adults in these studies suggests that developmental changes in insular functional connectivity might accompany the disorder 89,90 .…”
Section: Insula and Salience Dysfunctionmentioning
confidence: 71%
“…A recent study found that in children with ASD (aged 7-12 years old) there was a hyperconnectivity of the insula-based salience network 27 . The shift from the hyperconnectivity seen in younger children to hypoconnectivity seen in adolescents and adults in these studies suggests that developmental changes in insular functional connectivity might accompany the disorder 89,90 .…”
Section: Insula and Salience Dysfunctionmentioning
confidence: 71%
“…Recent meta-analyses investigating social dysfunction in ASD have implicated atypical activation patterns related to a broad range of social tasks. For example, Di Martino et al (2008) found that the ACC and the right anterior insula showed hypo-activation in ASD across a number of studies of social processing, while Dickstein et al (2013) found hypo-activation of the right STG across a number of social studies. Finally, a recent metaanalysis of the ASD face perception literature by Nickl-Jockschat et al (2014) reported hypo-activation of the left FG that was functionally hypo-connected with the IFG and temporo-occipital cortex across a number of studies.…”
Section: Tying It Together: Face Processing and Social Brain Netwmentioning
confidence: 99%
“…In particular, the study found greater reductions in activation in the parahippo campal gyrus, hippocampus and superior temporal gyrus in children with ASD compared with adults with ASD for social tasks, and increased hyperactivation in the right insula, right middle frontal gyrus and left cingulate for nonsocial tasks [113]. Thus, there are greater activation differences in children with ASD compared with their normal developing peers, and, with age, these differences seem to abate [113].…”
Section: Future Science Groupmentioning
confidence: 77%
“…Advancing our understanding of the brain in autism REVIEW Nevertheless, a recent meta-analysis specifically comparing fMRI studies of children and adults showed greater hyper-and hypo-activation in children with ASD compared with adults with ASD [113]. In particular, the study found greater reductions in activation in the parahippo campal gyrus, hippocampus and superior temporal gyrus in children with ASD compared with adults with ASD for social tasks, and increased hyperactivation in the right insula, right middle frontal gyrus and left cingulate for nonsocial tasks [113].…”
Section: Future Science Groupmentioning
confidence: 99%